Specialist valve clinic in a cardiac centre: 10-year experience. Issue 1 (20th April 2020) - Chambers, John B; Parkin, Denise; Rimington, Helen; Subbiah, Sheila; Campbell, Brian; Demetrescu, Camelia; Hayes, Anna; Rajani, Ronak
Abstract : Aims: Guidelines recommend specialist valve clinics as best practice for the assessment and conservative management of patients with heart valve disease. However, there is little guidance on how to set up and organise a clinic. The aim of this study is to describe a clinic run by a multidisciplinary team consisting of cardiologists, physiologist/scientists and a nurse. Methods: The clinical and organisational aims of the clinic, inclusion and exclusion criteria, and links with other services are described. The methods of training non-clinical staff are detailed. Data were prospectively entered onto a database and the study consisted of an analysis of the clinical characteristics and outcomes of all patients seen between 1 January 2009 and 31 December 2018. Results: There were 2126 new patients and 9522 visits in the 10-year period. The mean age was 64.8 and 55% were male. Of the visits, 3587 (38%) were to the cardiologists, 4092 (43%) to the physiologist/scientists and 1843 (19%) to the nurse. The outcomes from the cardiologist clinics were cardiology follow-up in 460 (30%), referral for surgery in 354 (23%), referral to the physiologist/scientist clinic in 412 (27%) or to the nurse clinic in 65 (4.3%) and discharge in 230 (15%). The cardiologist needed to see 6% from the nurse clinic and 10% from the physiologist/scientist clinic, while advice alone was sufficient in 10% and 9%. Conclusion: A multidisciplinary specialist valve clinic is feasible and sustainable in the long term.